An overview of PAX1: Expression, function and regulation in development and diseases - Wu, Weiyin; Kong, Xiangjun; Jia, Yanhan; Jia, Yihui; Ou, Weimei; Dai, Cuilian; Li, Gang; Gao, Rui (Frontiers in Cell and Developmental Biology, 2022)
Transcription factors play multifaceted roles in embryonic development and diseases. PAX1, a paired-box transcription factor, has been elucidated to play key roles in multiple tissues during embryonic development by extensive studies. Recently, an emerging role of PAX1 in cancers was clarified. Herein, we summarize the expression and functions of PAX1 in skeletal system and thymus development, as well as cancer biology and outline its cellular and molecular modes of action and the association of PAX1 mutation or dysregulation with human diseases, thus providing insights for the molecular basis of congenital diseases and cancers.